The Effects of O2O Service Factors on Sequel Service Adoption: O2O Service Quality Dimensions and Perceived Fit - Dayoung Kang; Seongcheol Kim (International Telecommunications Society (ITS), 2018)
As the mobile-based O2O industry grows, many existing O2O service providers are attempting to expand their businesses by service diversification. According to this trend, the current study investigated the effects of the parent O2O service-related factors on the user adoption of a sequel service. Specifically, a total of ten dimensions encompassing the whole service delivery process that flows from a convenient mobile app to an offline area were identified. Another factor that this study considered is users' fit perception between the parent and the sequel O2O service. To empirically test the conceptual model, this study carried out analyses for two different types of service: a food delivery (Case 1) and taxi-hailing O2O service (Case 2). The findings were drawn from a total of 444 South Korean respondents who have experience with using the parent O2O services but not with the sequel services. Results found that, for Case 1, informativeness and security of online service quality, and reliability and empathy of offline service quality were significant antecedents of satisfaction with the O2O service. For Case 2, efficiency of online service quality, ubiquity of O2O-specific service quality, and empathy were found to significantly affect O2O satisfaction. Results of both cases showed that perceived fit was a significant antecedent of intention to use a sequel service when attitude toward a service extension mediated. O2O satisfaction was found to be a crucial element influencing both O2O loyalty and intention to use a sequel service.
Keywords: 330; O2O service; Perceived service quality; Perceived fit; Loyalty; Intention to use